Wavelength-Scale Photonic Space Switch Proof-Of-Concept Based on Photonic Hook Effect; Annalen der Physik; Vol. 533 - Geynts Yu. E. Yury Elmarovich; Minin O. V. Oleg Vladilenovich; Yue Liyang; Minin I. V. Igor Vladilenovich (2021, 2021)
Title screen